The Intellectual Capital as a Measure of the Post-War Performance of Lebanese Banks - El Khatib, Anis; Al-khoury, Pierre (Archives of Business Research, 2019)
This is the first study to analyze the relationship between the Intellectual Capital (IC) and financial performance of the Lebanese Banking Sector. The study covers a 15 years period after the end of the Lebanese civil war, that is from 1990 to 2004.The consolidated financial statements of the all banks are analyzed. The Intellectual Capital performance of banks is measured through the value added intellectual coefficient (VAIC) methodology as developed by Pulic in 1998 and 2002. ROE and ROA are used as indicators for the financial performance of banks. Regression models are developed and ANOVA test is applied. The results showed that SCE, HCE, and CEE had a high significant explanatory power of the variations in the VAIC, with a dominating effect of the CEE. The results also showed a significant effect of the VAIC on performance as measured by ROA, and an insignificant effect on performance as measured by ROE. When the VAIC is divided into its components, it can be observed that the CEE has the most significant effect on banks performance measured by both ROA and ROE. Lebanese banks are encouraged to start using the IC and other performance measurement systems (PMS’s), and not limiting their work only to financial measures to judge performance.